Digging up Jericho: past, present and future - Sparks, Rachael Thyrza; Finlayson, Bill; Wagemakers, Bart; Briffa, Josef Mario (Archaeopress, 2020)
21 papers present a holistic perspective on the research and public value of the site of Jericho - an iconic site with a long and impressive history stretching from the Epipalaeolithic to the present day. Covering all aspects of archaeological work from past to present and beyond, they re-evaluate and assess the legacy of this important site